Where did you "left" Piazza del Popolo? At your "right" temporo-parietal junction. (December 2015) - Committeri, Giorgia; Piccardi, Laura; Galati, Gaspare; Guariglia, Cecilia
Abstract: Humans have an advanced ability to recall places and scenes from memory, which they scan with their "mind's eye" in order to cope with daily demands such as navigating and learning new environments. In the striking neurological syndrome called representational or imaginal neglect, patients with right brain damage fail to report contralesional, left-sided elements of familiar places relative to their imaginary vantage point. Notwithstanding descriptions of single cases of representational neglect dissociated from perceptual or visual neglect, it is still unknown whether this disorder is due to specific brain lesions. Here we show that the ability to properly recall and inspect places from memory is supported by a neural network dissociated from that necessary to properly scan single objects from memory or the external visual world. Lesion-symptoms mapping of 40 right-damaged patients with and without imaginal neglect identified a peak region located at the posterior junction between the parietal and temporal lobes (pTPJ), where the angular and supramarginal gyri abut on the posterior temporal cortex. This region is known to support first-person perspective transformations and is connected with systems relevant for navigation and retrieval from autobiographical memory. Our results provide new insights on human spatial memory and imagery and their relationship with visuospatial attention, directly affecting recent neural and computational models. Graphical abstract: